2021
DOI: 10.1007/s12291-021-00972-3
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach of the Potential Underlying Molecular Mechanistic Paradigms of SARS-CoV-2-Mediated Coagulopathy

Abstract: Coronavirus disease 2019 (Covid-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a pandemic disease which has affected more than 6.2 million people globally, with numbers mounting considerably daily. However, till date, no specific treatment modalities are available for Covid-19 and also not much information is known about this disease. Recent studies have revealed that SARS-CoV-2 infection is associated with the generation of thrombosis and coagulopathy. Fundamentally, it has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…The cytokine storm is characterized by high serum levels of various cytokine mixtures, such as IL-1β, IL-6, IL-7, IL-8, IL-9, IL-10, IL-18, IL-33, FGF (fibroblast growth factor), G-CSF (granulocyte-colony stimulating Factor), GM-CSF (granulocyte-macrophage colony-stimulating factor), IFN-γ (interferon-γ), CCL-2 (CC-chemokine ligand 2), IP-10 (interferon-gamma induced protein 10), MCP-1, MIP-1β (Macrophage Inflammatory Protein 1β), PDGF (platelet-derived growth factor), TNF-α, and VEGF [ 181 , 182 ]. These mixed cytokine stews are pro-coagulatory in nature and induce multiple pathways associated with fibrin generations, including platelet activation and aggregation, activation of coagulation factors and complement components, renin-angiotensin system and tissue-resident macrophages [ 183 , 184 ]. In particular, proinflammatory cytokines, IL-1ß, IL-6, IL-8 and TNF-α, resulted in platelet hyperactivation with increased clumps, suggesting that these molecules possess profound effect on rumpled fibrin clot with trapped RBCs [ 185 , 186 ].…”
Section: Sars-cov-2 and Its Receptors In Blood Vessel Pathophysiologymentioning
confidence: 99%
“…The cytokine storm is characterized by high serum levels of various cytokine mixtures, such as IL-1β, IL-6, IL-7, IL-8, IL-9, IL-10, IL-18, IL-33, FGF (fibroblast growth factor), G-CSF (granulocyte-colony stimulating Factor), GM-CSF (granulocyte-macrophage colony-stimulating factor), IFN-γ (interferon-γ), CCL-2 (CC-chemokine ligand 2), IP-10 (interferon-gamma induced protein 10), MCP-1, MIP-1β (Macrophage Inflammatory Protein 1β), PDGF (platelet-derived growth factor), TNF-α, and VEGF [ 181 , 182 ]. These mixed cytokine stews are pro-coagulatory in nature and induce multiple pathways associated with fibrin generations, including platelet activation and aggregation, activation of coagulation factors and complement components, renin-angiotensin system and tissue-resident macrophages [ 183 , 184 ]. In particular, proinflammatory cytokines, IL-1ß, IL-6, IL-8 and TNF-α, resulted in platelet hyperactivation with increased clumps, suggesting that these molecules possess profound effect on rumpled fibrin clot with trapped RBCs [ 185 , 186 ].…”
Section: Sars-cov-2 and Its Receptors In Blood Vessel Pathophysiologymentioning
confidence: 99%
“…This induction of VEGFA tissue expression was attributed mainly to the cytokine storm process and to the COVID-19-related hypoxia state, which can induce a pro-angiogenic response. However, this angiogenic stimulus appears to be responsible for an increase of endothelial lung cell permeability that further impairs endothelium function and triggers tissue factor (TF) release, which leads to the establishment of a pro-thrombotic environment, [35][36][37][38] once this interaction, in theory, could minimize the angiogenesis process and avoid organ damage. Thus, considering that our results showed that miR-205-5p is present in the serum of patients who presented non-fatal and fatal COVID-19, but significantly upregulated in the last cohort, we hypothesize that miR-205-5p could be involved in the COVID-19 pathophysiology both as an inducer of inflammation and as a cell regulator released in response to VEGFA over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the virus and the ACE-2 receptors yields an imbalanced shift, inducing inflammation, vasoconstriction, and coagulation cascade. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%